Supervision as One of the Elements of Educational Resource Development - Yana, Leli; Mukti; Rinawati, Maida; Destriyati; Salim, Amil; Harto, Kasinyo; Astuti, Mardiah (The Future of Education Journal, 2024)
This study aims to analyze supervise as one of the elements of educational resource development as an effort to improve the quality of learning in educational institutions based on Islamic values. The research method used is qualitative using literature study or library research, by managing and analyzing reference sources from articles, journals, and other sources from the internet. The results of this study show that effective supervision management involves Islamic principles such as deliberation, amar ma'ruf nahi munkar, and example, and is supported by continuous evaluation and coaching. Supervision carried out with an Islamic approach has been proven to improve teachers' pedagogic competence, learning quality, and the achievement of Islamic education goals holistically.